VARICELLA ZOSTER VIRAL RETINITIS IN A PATIENT WITH SYSTEMIC LUPUS ERYTHEMATOSIS - Nagaraj, Kalpana Badami; Muralidhar, Sonali; Jayadev, Chaitra; Kirthiraj (Journal of Health and Allied Sciences NU, 2015)
A young female a known case of systemic lupus erythematosus who underwent renal transplantation for end stage lupus nephritis was on long term immunosuppression for her systemic condition. She had an episode of varicella three months before she presented to us with ocular complaints in the right eye. She was diagnosed to have progressive outer retinal necrosis with a differential of cytomegaloviral retinitis in the right eye and treatment was initiated. She had begun to show improvement in visual acuity but within two weeks her systemic condition worsened rapidly and she succumbed to septic shock.The ocular infection in an immunocompromised SLE patient can be a precursor of mortality as seen in our patient.Due consideration is to be given for prophylactic treatment post varicella infection along with a multidisciplinary approach in managing the immunocompromised, to prevent devastating complications or mortality.
Keywords: Viral retinitis; immunosuppressants; systemic lupus